2001
DOI: 10.1590/s0034-72992001000600005
|View full text |Cite
|
Sign up to set email alerts
|

Análise acústica da voz captada na faringe próximo à fonte glótica através de microfone acoplado ao fibrolaringoscópio

Abstract: Palavras-chave: distúrbios da voz, qualidade da voz, glote, laringoscopia, análise acústica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
6
2
13
Order By: Relevance
“…of F 0 in Brazilian Portuguese speaking men and without vocal alterations, it was observed that the result was similar to a study (F 0= 109,05) 14 . On the other hand, other studies have found fundamental frequency higher than those obtained in the present study, in normal voices (F 0 =120Hz) 26 ; standardizing the fundamental frequency in a developed program by the Engineering School of São Carlos (F 0 =127,61Hz) 27 , and to analyze the operation and the type of voice in different microphone positions (F 0 =130,19Hz) 28 . The difference suggests that the dentofacial condition can influence the position of the larynx, and also in the fundamental frequency.…”
Section: Acknowledgementscontrasting
confidence: 60%
“…of F 0 in Brazilian Portuguese speaking men and without vocal alterations, it was observed that the result was similar to a study (F 0= 109,05) 14 . On the other hand, other studies have found fundamental frequency higher than those obtained in the present study, in normal voices (F 0 =120Hz) 26 ; standardizing the fundamental frequency in a developed program by the Engineering School of São Carlos (F 0 =127,61Hz) 27 , and to analyze the operation and the type of voice in different microphone positions (F 0 =130,19Hz) 28 . The difference suggests that the dentofacial condition can influence the position of the larynx, and also in the fundamental frequency.…”
Section: Acknowledgementscontrasting
confidence: 60%
“…Alguns aspectos da voz são primários da laringe e outros são contribuições do filtro do trato vocal [9][10][11] . Existem diferenças anatômicas e fisiológicas entre o organismo dos homens e das mulheres que resultam em características capazes de diferenciar os dois sexos.…”
Section: Revisão Da Literatura O Aparelho Fonador E a Voz No Homemunclassified
“…[10][11]16 . Diversos estudos relatam a ação modificadora do filtro vocal sobre o sinal vocal produzido pelas pregas vocais [9][10][11]16 . A espectrografia pode ser descrita como um gráfico tridimensional que apresenta em sua ordenada a frequência, em sua abscissa o tempo, e seu grau de escurecimento do traçado relaciona-se com a intensidade.…”
Section: Características Vocais Acústicas De Vozes Masculinas: Caractunclassified
See 1 more Smart Citation
“…Each subject was asked to stand with arms extended along the body; the digital recorder was placed 4 cm from the subject's mouth. 3,4,5,6 The subject was asked to breath in deeply and to issue the sustained phoneme /a/ at a typical (normal voice) speech height, intensity, quality and velocity. 3,[6][7][8][9] These voice samples were sent to four referees who were speech therapists with at least five years experience in voice evaluation, who did not know the purposes of the study, and who analyzed the voices independently, without knowing about the remaining referees.…”
Section: Methodsmentioning
confidence: 99%